Application of Technology Acceptance Model and Delone and McLean IS Success Model to Measure Information System Design for Academic Activities in Higher Education Institution - Sri Wahyuningsih, Suluh; Herli Sumerli A, Chevy; Rahayu, Novi; Nuryanto, Uli Wildan; Ramadhani, Budi (SEULANGA SYSTEM PUBLISHER, 2024)
The purpose of this study is to investigate the variables that may affect how well the academic information system performs. Quantitative approaches are employed in this study. The basic random sampling technique was used in this study to get samples from the community of academic information system users. There were 100 samples used in this investigation. The Technology Acceptance Model (TAM) and the Delone & Mclean model are used in this study. In this study, questionnaires were distributed as part of the data collection process. The SmartPLS was used in this study's inferential statistical analysis. According to the analysis results, introducing elements that have the biggest impact namely, perceived ease of use and service quality should be prioritized in order to improve helpdesk services in academic information systems. This involves establishing a report ticket function to resolve user complaints and offer updates on problem resolution, as well as optimizing academic information system for mobile displays to promote simple access to various academic information system -related demands. Perceived ease of use on perceived usefulness (path coefficient value: 0.79); service quality on perceived ease of use (path coefficient value: 0.79); user satisfaction on net benefits (path coefficient value: 0.74); and system quality on net benefits (path coefficient value: 0.03), are the variables that have the biggest influence in this research.